Knowledge, Awareness, and Perception of Dental Stem Cell: A Questionnaire-based Cross-sectional Study - Cox Shireen; Anitha K; Karthik R Murali; Aishwarya K; Gokul S; Moulvi S. M. M (Wolters Kluwer Medknow Publications, 2024)
The purest and unrestricted source of stem cells is the enamel of the teeth. Dental stem cells (DSCs), which are simple to get, quick to use, and reasonably priced, have the potential to be used in a variety of promising therapeutic applications. Due to their capacity for self-renewal, they are employed to treat significant flaws brought about by diseases, injuries, or surgical procedures. However, they are constrained by moral and ethical issues, as well as challenges with isolation, culturing, and implantation. DSCs are used in the rebuilding of orofacial structures because they retain the ability to differentiate into neurogenic, adipogenic, and odontogenic components. Before stem cell implantation, scaffolding that has been treated with growth hormones and bone morphogenic proteins is crucial. A self-administered questionnaire was used for a cross-sectional study (n = 200) that collected data on demographics, knowledge of stem cells, and attitude statements. Statistical Package for Social Software version 20.0 was used to analyze the data. This study seeks to learn more about professional groups' perceptions of stem cell research in Tamil Nadu and their knowledge and awareness of DSCs.